Pendampingan Ibu Dalam Menstimulasi Perkembangan Motorik Untuk Mengoptimalkan Tumbuh Kembang Balita di Posyandu Desa Paberasan - Nelia Damayanti, Cory; Wardita, Yulia; Meiri Kurniyati, Eka (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
This service is carried out in Paberasan Village, Sumenep City District, Sumenep Regency. This community service aims to provide knowledge about the stimulation of motor development in optimizing growth and development. This service is carried out by providing direct counseling during the implementation of the Toddler Posyandu because we consider it very effective because at that time all mothers and toddlers are present. Presentation of material in dialogue and to make it more interesting is assisted by educational videos so that it can be more interesting and makes mothers realize the importance of stimulating motor development for toddlers. The results of the activity showed a very good response from the mother with a positive response from the mother, seen from her enthusiasm to ask and explain what was conveyed during the counseling. Counseling on motor development stimulation can provide convenience for toddlers to optimize their toddler development so that toddlers can develop according to their stages of development.